Effect of light-activation on the antibacterial activity of dentin bonding agents - Duque, Cristiane; Negrini, Thaís de Cássia [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Hebling, Josimeri [UNESP] (My University, 2010)
Aim: This study evaluated the effect of light-activation on the antibacterial activity of dentin bonding systems. Methods: Inocula of Streptococcus mutans and Lactobacillus casei cultures were spread on the surface of BHI agar and the materials were applied and subjected or not to light-activation. Zones of bacterial growth inhibition around the discs were measured. Results: Excite, Single Bond and the bond of Clearfil SE Bond (SE) and Clearfil Protect Bond (CP) did not show any antibacterial activity. The strongest inhibitory activity was observed for the primers of CP and Prompt (PR) against S. mutans and the primers of SE and PB against L. casei. Conclusion: Light-activation significantly reduced or suppressed the antibacterial activity of the initially active uncured dentin bonding systems.
Keywords: Dentin bonding systems; Antibacterial activity; Streptococcus mutans; Lactobacillus casei